Microstructural Representation of Nationally Marked Units in Scots-English and Gaelic-English Dictionaries - Лемещенко-Лагода, Вікторія Володимирівна; Lemeshchenko-Lagoda, Viktoriia (Київ : УДУ імені Михайла Драгоманова, 2023)
EN: The article presents the results of a comprehensive analysis of dictionary entries of nationally marked units in Scots-English and Gaelic-English dictionaries. For the first time, the dictionary entries for nationally marked units of the minority languages of Scots and Scottish Gaelic were analysed. The main microstructural components were considered and the main approaches to dictionary entries compiling were highlighted. The analysis of the vocabulary entries of nationally marked units in Scots-English and Gaelic-English dictionaries has revealed both common and distinctive features. Among the common features it is worth mentioning the presence of such components as headword, synchronic data, diachronic data, marking, explanatory data, syntagmatic data, illustrations and examples. Dictionary entries of nationally marked units in Scots-English dictionaries are distinguished by the presence of more complete data presentation, detailed explanations, as compared to the corresponding dictionary entries in Gaelic-English dictionaries. On average, a dictionary entry for a nationally marked unit in a Scots-English dictionary includes up to seven or eight microstructure components, while a dictionary entry in a Gaelic-English dictionary includes from three to five components. At the same time, the interpretation of a nationally marked unit in Scots-English dictionaries is more rational due to the joint presentation of the interpretation and the equivalent in the target language, whereas Gaelic-English dictionaries only provide equivalents. The absence of illustrative examples for nationally marked units in Gaelic-English dictionaries is also considered as one of distinctive features. UA: У статті представлено результати комплексного аналізу словникових статей національно маркованих одиниць у шотландсько (cкотс)-англійських та гельсько-англійських словниках. Уперше проаналізовано словникові статті до національно маркованих одиниць міноритарних мов Шотландії – скотс шотландської гельської. Розглянуто основні мікроструктурні компоненти та виокремлено основні підходи до укладання словникових статей національно маркованих одиниць міноритарних мов. Аналіз словникових статей національно маркованих одиниць у шотландсько (скотс)-англійських та гельсько-англійських словниках виявив як спільні, так і відмінні риси. Серед спільних рис варто відзначити наявність таких компонентів, як заголовне слово, синхронні дані, діахронні дані, маркування, пояснювальні дані, синтагматичні дані, ілюстрації та приклади. Словникові статті національно маркованих одиниць у шотландсько (скотс)-англійських словниках вирізняються наявністю більш повного представлення даних, детальних пояснень та тлумачень, порівняно з відповідними словниковими статтями до національно маркованих одиниць у гельсько-англійських словниках. Тому в середньому словникова стаття національно маркованої одиниці в шотландсько (скотс)- англійському словнику включає до семи-восьми компонентів мікроструктури, тоді як словникова стаття національно маркованої одиниці в гельсько-англійському словнику складається з трьох-п’яти мікроструктурних компонентів. При цьому тлумачення національно маркованої одиниці в шотландсько (скотс)-англійських словниках є більш раціональним завдяки спільному поданню власне розгорнутого тлумачення та еквівалента мовою перекладу, тоді як гельсько-англійські словники подають лише еквіваленти мовою перекладу. Відсутність ілюстративних прикладів використання національно маркованих одиниць у ситуативному мовленні у гельсько-англійських словниках також вважається однією з відмінних рис.
Мікроструктурна репрезентація національно маркованих одиниць у шотландсько (cкотс)-англійських та гельсько-англійських словниках
Keywords: nationally marked units; microstructure; dictionary entry; Scots-English dictionaries; Gaelic-English dictionaries; lexicography; націоально марковані одиниці; мікроструктура; словникова стаття; скотс-англійські словники; гельсько-англійські словники; лексикографія